Margins of Learning: A Critical Analysis of the Scholia on Apollonius' Argonautica - Doyle, Lisa Amy (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2024)
The scholia on Apollonius’ Argonautica constitute a substantial and varied corpus but have been overlooked by modern scholarship. This thesis seeks to fill that gap by providing a critical evaluation of the Argonautica scholia, which establishes the nature and value of the corpus. In this thesis, I examine the literary-critical features of the corpus, highlighting the unique critical terminology and the preoccupation with analysing speeches and characters in Book 1. I study the comments concerned with language and grammar which show that some of Apollonius’ readers monitored his text in order to identify ‘errors’, particularly in relation to his use of certain pronouns. The citations and references to other authors in the Argonautica scholia are one of the hallmarks of this corpus. I analyse the references to a selection of authors throughout the corpus, contextualizing the citations and fragments within the whole scholion and corpus of which they are a part. I argue that certain authors are prioritized, resulting in a hierarchy of authorities. The overarching interest in mythological content in this corpus results in the elucidation of myth and local histories and comments on realia. This interest is examined through case studies which demonstrate that Apollonius’ commentators orient themselves in the text by mapping mythical places onto known locations, collating genealogies and foundation myths, and cataloguing geographical landmarks such as rivers. Throughout my analysis, I indicate parallels with other scholia corpora (particularly the Homeric scholia) and identify types of scholarship and scholarly discourses which shed light on the commentary tradition from which the scholia derive.
APPROVED
Keywords: Ancient Greek Literature; Scholia; Hellenistic Poetry; Argonautica